(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
The COVID-19 pandemic is a major loss event for the insurance industry. This chapter begins with an overview of the pandemic’s most significant insurance implications. Because business interruption has been the most prominently discussed of these impacts, the second part of this chapter takes a closer look at business interruption insurance. This part describes how markets for this coverage are structured in the U.S., and then undertakes a detailed analysis of one of the most common business interruption policy forms, demonstrating that some aspects of this form, insofar as pandemic-caused business interruption is concerned, were not drafted with utmost precision. This part also discusses how disputes over common policy language used in the U.S. have unfolded, both in legislatures and the courts. The chapter concludes with a discussion of the future of insuring the business continuity risk. It explores the limitations of private markets, the role of government, and the need for an overarching strategy for pandemic risk management, within which insurance would play a significant but partial role.